2001
DOI: 10.1111/j.1365-2621.2001.tb04632.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Classification of Streptococcus Thermophilus and Lactobacillus Delbrueckii Subsp. Bulgaricus Strains Isolated from Traditional Greek Yogurts

Abstract: Streptococcus thermophilus (74 strains) and Lactobacillus delbrueckii subsp. bulgaricus (75 strains) isolates from traditional Greek yogurts were tested on the basis of their acidification kinetics, acidity, viscosity, and aroma compounds formation in milk pure cultures. Strains of Lb. bulgaricus presented greater viscosity values, higher acidification activity and produced more acetaldehyde at culture pH 4.6 than S. thermophilus strains. Acetoin was formed only by the latter strains, while diacetyl was not de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 18 publications
1
24
5
Order By: Relevance
“…II), which contrasts with most reports on acetaldehyde [8,28,32]. This may have resulted from the larger final populations of S. thermophilus than of Lb.…”
Section: Effect Of the S Thermophilus/lb Bulgaricus Association On contrasting
confidence: 53%
“…II), which contrasts with most reports on acetaldehyde [8,28,32]. This may have resulted from the larger final populations of S. thermophilus than of Lb.…”
Section: Effect Of the S Thermophilus/lb Bulgaricus Association On contrasting
confidence: 53%
“…The most important ingredients of cow milk required by the yoghurt starter cultures to produce acetaldehyde are lactose (mainly the glucose fraction) and the amino acids threonine and methionine. The content of acetaldehyde in yoghurt from cow milk usually ranged from 1.3-3.5 mg/kg (Xanthopoulos et al 2001) to 40 mg/kg (Ozer & Atasoy 2002). In this study, milk fermented only by the yoghurt culture contained 5.63 ± 0.36 mg/kg of acetaldehyde while in soymilk yoghurt 3.84 ± 0.30 mg/kg of acetaldehyde was found.…”
Section: Resultsmentioning
confidence: 75%
“…In contrast, IMAU80846 showed a gradual increase in acetaldehyde during storage of 12-36 h. The breakdown of acetaldehyde during storage possibly resulted from the microbial enzymes driven-hydrolysis and may provide amino acids and nucleotides for maintaining the cell viability (Güler-akn, 2005). Similarly, Xanthopoulos et al (2001) observed the reduction of acetaldehyde in some S. thermophilus strains during fermented milk storage. Moreover, diacetyl, mainly produced by S. thermophilus, is another antibacterial compound potentially contributing to the yogurt aroma (Chammas et al, 2006;Kang and Fung, 1999;Routray and Mishra, 2011).…”
Section: Changes In Acetaldehyde Diacetyl Lactic Acid and Formic Acmentioning
confidence: 97%
“…Xanthopoulos et al (2001) reported that the acidification ability of S. thermophilus of 74 strains showed no obvious relation to the final amount of lactic acid produced. Formic acid is also an important metabolite of lactic acid fermentation and its production is strain-dependent (Perez et al, 1991).…”
Section: Changes In Acetaldehyde Diacetyl Lactic Acid and Formic Acmentioning
confidence: 99%